The Regional Western Sweden SOM Survey 1997 - SOM Institute, University of Gothenburg (University of Gothenburg, 1999)
This is the sixth study in the series of SOM-surveys carried out in Western Sweden exclusively. The questionnaire was divided into six subject fields: mass media; politics and society; the municipality of Göteborg; traffic and environment; leisure and media; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Detta är den sjätte studien i serien SOM-undersökningar genomförda i Västsverige. Brevenkäten var indelad i sex frågeområden: Massmedier; Politik och samhälle; Trafik och miljö; Fritid och medier; Tidningsläsande; samt Bakgrundsfrågor. Personer bosatta i Göteborgs kommun fick även ange inställning till åtta kommunala politiker samt om man känner till vilken stadsdelsnämnd man tillhör. De flesta frågorna är ställda i en eller flera tidigare Väst-SOM.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1997
Väst-SOM 1997
Keywords: internal politics; inrikespolitik; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap